Readmission in elective spine surgery: Will short stays be beneficial to patients. (August 2020) - Brown, Avery E.; Saleh, Hesham; Naessig, Sara; Pierce, Katherine E.; Ahmad, Waleed; Bortz, Cole A.; Alas, Haddy; Chern, Irene; Vasquez-Montes, Dennis; Ihejirika, Rivka C.; Segreto, Frank A.; Haskel, Jonathan; et al.
Highlights: Surgical spine patients with shorter LOS had increased rates of complications and readmissions. Patients with Clavien Grade 5 complications in 2015 had the lowest mean time to readmission. Negative outcomes may be diminished with careful patient selection. Abstract: There has been limited discussion as to whether spine surgery patients are benefiting from shorter in-patient hospital stays or if they are incurring higher rates of readmission and complications secondary to shortened length of stays. Included in this study were 237, 446 spine patients >18yrs and excluding infection. Patients with Clavien Grade 5 complications in 2015 had the lowest mean time to readmission after initial surgery in all years at 12.44 ± 9.03 days. Pearson bivariate correlations between LOS ≤ 1 day and decreasing days to readmission was the strongest in 2016.). Logistic regression analysis found that LOS ≤ 1 day showed an overall increase in the odds of hospital readmission from 2012 to 2016 (2.29 [2.00–2.63], 2.33 [2.08–2.61], 2.35 [2.11–2.61], 2.27 [2.06–2.49], 2.33 [2.14–2.54], all p < 0.001).